2020
DOI: 10.1155/2020/7409417
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Reward and Habit Systems by Acupuncture in Adolescents with Internet Addiction

Abstract: Purpose. Acupuncture is an effective therapy for Internet addiction (IA). However, the underlying mechanisms of acupuncture in relieving compulsive Internet use remain unknown. Neuroimaging studies have demonstrated the role of the ventral striatum (VS) in the progress of IA; hence, the aim of this study was to explore the effects of acupuncture on the resting-state functional connectivity (rsFC) and relevant network of VS in IA. Methods. Twenty-seven IA individuals and 30 demographically matched healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 70 publications
6
15
0
Order By: Relevance
“…Previous studies have confirmed that acupuncture has a regulatory effect on the structure and function of brain regions in substance addicts ( 17 , 18 ). Similarly, our previous findings suggest that acupuncture on PIU individuals can regulate functional connectivity of reward and habit systems ( 19 ), and this result is related to the current research results of Internet addiction ( 20 ). In a review study, Weinstein and Lejoyyeux ( 21 ) reported that Internet addiction is associated with the brain regions associated with reward and cognitive control network.…”
Section: Introductionsupporting
confidence: 78%
“…Previous studies have confirmed that acupuncture has a regulatory effect on the structure and function of brain regions in substance addicts ( 17 , 18 ). Similarly, our previous findings suggest that acupuncture on PIU individuals can regulate functional connectivity of reward and habit systems ( 19 ), and this result is related to the current research results of Internet addiction ( 20 ). In a review study, Weinstein and Lejoyyeux ( 21 ) reported that Internet addiction is associated with the brain regions associated with reward and cognitive control network.…”
Section: Introductionsupporting
confidence: 78%
“…The impulsive habit system in the tripartite neurocognitive model is responsible for fast, automatic, unconscious, and habitual behaviors (Wei et al, 2017). In the current study, the hyperfunction of the right PMC and bilateral cerebellum in individuals with IA, which were thought to contribute to the habitual or compulsive use of the internet, was detected and further found to contribute to IA identification and the evaluation of CBT efficacy (Wang et al, 2020a).…”
Section: Hyperactive Impulsive Habit Systemsupporting
confidence: 47%
“…In IA studies, increased activations in the cerebellum were also found in individuals with IA when exposed to internet cues, implicating automatic habitual reactions to internet (Schmitgen et al, 2020). Furthermore, the hyperactivity of the PMC-cerebellar loop was found both in IA and substance addiction (Yalachkov et al, 2009;Wang et al, 2020a), suggesting the common pathological changes in the habit system in IA and substance dependence.…”
Section: Hyperactive Impulsive Habit Systemmentioning
confidence: 90%
See 1 more Smart Citation
“…A number of studies have con rmed the central nervous system (CNS) plays a primary role in acupuncture effect [8][9][10] . Similar to other studies on brain function, neuroimaging technologies have been extensively employed into this area, such as functional Magnetic Resonance Imaging (fMRI) [11,12] , Positron Emission Tomography (PET) [13] , electroencephalography (EEG) [14] , and magnetoencephalography (MEG) [15] . A study has shown that fMRI and PET/PET-CT are the two most commonly used methods [16] .…”
Section: Rationalementioning
confidence: 99%